2020
DOI: 10.1002/ece3.6349
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of sickness behavior in immune‐challenged field crickets

Abstract: Sickness behavior is a taxonomically widespread coordinated set of behavioral changes that increases shelter‐seeking while reducing levels of general activity, as well as food (anorexia) and water (adipsia) consumption, when fighting infection by pathogens and disease. The leading hypothesis explaining such sickness‐related shifts in behavior is the energy conservation hypothesis. This hypothesis argues that sick (i.e., immune‐challenged) animals reduce energetic expenditure in order have more energy to fuel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…While sickness behaviors have historically been studied in the context of vertebrate physiology, more work has been done to identify their presence and importance in invertebrates. As mentioned previously, these behaviors confer advantage for survival, and thus have evolved to be present in many species, including field crickets [Jacot et al, 2004;Kelly and Leroux, 2020], honeybees [Kazlauskas et al, 2016], caterpillars [Adamo et al, 2007], fruit flies Jardine, 2015, 2017;Surendran et al, 2017], Caenorhabditis elegans [Singh and Aballay, 2019], and many others.…”
Section: Sickness Behaviors Across Speciesmentioning
confidence: 96%
See 1 more Smart Citation
“…While sickness behaviors have historically been studied in the context of vertebrate physiology, more work has been done to identify their presence and importance in invertebrates. As mentioned previously, these behaviors confer advantage for survival, and thus have evolved to be present in many species, including field crickets [Jacot et al, 2004;Kelly and Leroux, 2020], honeybees [Kazlauskas et al, 2016], caterpillars [Adamo et al, 2007], fruit flies Jardine, 2015, 2017;Surendran et al, 2017], Caenorhabditis elegans [Singh and Aballay, 2019], and many others.…”
Section: Sickness Behaviors Across Speciesmentioning
confidence: 96%
“…In addition to humans, changes in social motivation in response to sickness have been described in many other animals. Social vocalizations in passerine birds [Garamszegi et al, 2004], field crickets [Jacot et al, 2004;Kelly and Leroux, 2020], and vampire bats [Stockmaier et al, 2020] have all been studied in the context of immune challenge. In all cases, infection causes a decrease in social contacts, which can be interpreted as social withdrawal.…”
Section: Social Changes In Sickness Behaviorsmentioning
confidence: 99%
“…Interestingly, although mating grants females an immune advantage and there is little evidence of sickness behavior in field crickets (Kelly & Mc Cabe Leroux, 2020 ; Sullivan et al, 2016 ), we found that immune‐challenged adults exhibited decreased rates of mating and consequently lower egg viability compared to healthy females. These findings confirm that illness just prior to a mating opportunity can have significant negative impacts on female fitness beyond those predicted by resource constraints alone.…”
Section: Discussionmentioning
confidence: 53%